73‐2: Invited Paper: High‐Performance Quantum Dot Light Emitting Diodes and their Challenges. Issue 1 (30th May 2018) - Acharya, Krishna P.; Titov, Alexandre; Ying, Chen Y.; Hyvonen, Jake; Holloway, Paul H.
Abstract : Displays made using colloidal quantum dots as electroluminescent (EL) emitter is a very promising display technology because it is efficient, emits pure color, and is inexpensive. We have demonstrated highly efficient red, green, and blue quantum dot light emitting diodes (QLEDs) using a colloidal zinc oxide nanoparticle electron transport layer. Here, we will report QLEDs with external quantum efficiency >15% for red, green, and blue color (approaching the theoretical‐limit of 22% for green) QLEDs. Finally, we will discuss some of the challenges that must be addressed to successfully commercialize EL‐QLED displays.